The rice cation/H+ exchanger family involved in Cd tolerance and transport - Zou, Wenli; Chen, Jingguang; Meng, Lijun; Chen, Dandan; He, Haohua; Ye, Guoyou (MDPI, 2021)
Cadmium (Cd), a heavy metal toxic to humans, easily accumulates in rice grains. Rice with unacceptable Cd content has become a serious food safety problem in many rice production regions due to contaminations by industrialization and inappropriate waste management. The development of rice varieties with low grain Cd content is seen as an economic and long-term solution of this problem. The cation/H+ exchanger (CAX) family has been shown to play important roles in Cd uptake, transport and accumulation in plants. Here, we report the characterization of the rice CAX family. The six rice CAX genes all have homologous genes in Arabidopsis thaliana. Phylogenetic analysis identified two subfamilies with three rice and three Arabidopsis thaliana genes in both of them. All rice CAX genes have trans-member structures. OsCAX1a and OsCAX1c were localized in the vacuolar while OsCAX4 were localized in the plasma membrane in rice cell. The consequences of qRT-PCR analysis showed that all the six genes strongly expressed in the leaves under the different Cd treatments. Their expression in roots increased in a Cd dose-dependent manner. GUS staining assay showed that all the six rice CAX genes strongly expressed in roots, whereas OsCAX1c and OsCAX4 also strongly expressed in rice leaves. The yeast (Saccharomyces cerevisiae) cells expressing OsCAX1a, OsCAX1c and OsCAX4 grew better than those expressing the vector control on SD-Gal medium containing CdCl2. OsCAX1a and OsCAX1c enhanced while OsCAX4 reduced Cd accumulation in yeast. No auto-inhibition was found for all the rice CAX genes. Therefore, OsCAX1a, OsCAX1c and OsCAX4 are likely to involve in Cd uptake and translocation in rice, which need to be further validated.